STUDI FAKTOR YANG MEMENGARUHI PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PADA INVESTOR DI KOTA DENPASAR - Dewi, Made Intan Berliana Lestari; Wiagustini, Ni Luh Putu (Buletin Studi Ekonomi, 2022)
This study aims to determine the effect of financial literacy, locus of control, psychological factors, and demographic factors on stock investment decisions. The population of this study is stock investors listed on the Indonesia Stock Exchange and located in Denpasar City. The number of samples taken was 100 respondents, based on the purposive sampling technique, and collected by using a questionnaire. The analytical method used is PLS-based SEM with SmartPLS 3.0 application. The results showed that financial literacy, locus of control, psychological factors, and demographic factors had a significant positive influence on stock investment decisions. Female investors and investors with a young age are more daring to make investment decisions. Based on the results of this study, stock investors in Denpasar City have considered financial literacy, locus of control, psychological factors, and demographic factors in making stock investment decisions to avoid investment risks and get high returns.